Applying the smart city philosophy in Brazil for improving urban traffic condition by agent-based simulation - Pereira, Wilson Inacio; Chwif, Leonardo (Brazilian Journal of Operations & Production Management, 2017)
Urban mobility improvement as part of smart city philosophy is an extreme importance issue in large urban centers, mainly for its influence over economic and social development. The main objective of this work is to develop a mobility study of automotive vehicles in Goiás Avenue, the main avenue of São Caetano do Sul, Brazilian city with the highest Human Development Index (HDI). Three alternative scenarios for traffic improvement were studied using an agent-based simulation model: Speed Reduction, Green Wave Implementation and a mixed scenario that combines these two approaches. The main results evaluated were average vehicle crossing time, average time spent in queues and total number of vehicles that leave the system during rush hours. It was concluded that, among the proposed scenarios, a mixed one should be implemented as it has favorable results in all of the studied performance indicators and maximizes the benefits generated by the other two scenarios. It is expected that the results of this study will serve to encourage further research in this area and give continuity to the idea of a digital city.